2000
DOI: 10.4049/jimmunol.164.12.6453
|View full text |Cite
|
Sign up to set email alerts
|

A Filarial Nematode-Secreted Product Signals Dendritic Cells to Acquire a Phenotype That Drives Development of Th2 Cells

Abstract: Although exogeneous “danger” signals such as LPS can activate APC to produce a Th1 response, the nature of events initiating a Th2 response is controversial. We now show that pathogen-derived products have the capacity to induce bone marrow-derived dendritic cell cultures to acquire a phenotype that promotes the differentiation of naive CD4+ T cells toward either a Th1 or Th2 phenotype. Thus, LPS-matured dendritic cells (DC1) promote a Th1 response (increased generation of IFN-γ and reduced production of IL-4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
283
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(302 citation statements)
references
References 29 publications
17
283
2
Order By: Relevance
“…In addition to these indirect effects, microorganisms also directly affect sentinel DCs at the time of pathogen encounter, as has been shown previously (1)(2)(3)(4).…”
Section: Microbial Compounds Selectively Induce Th1 Cell-promoting Ormentioning
confidence: 66%
See 1 more Smart Citation
“…In addition to these indirect effects, microorganisms also directly affect sentinel DCs at the time of pathogen encounter, as has been shown previously (1)(2)(3)(4).…”
Section: Microbial Compounds Selectively Induce Th1 Cell-promoting Ormentioning
confidence: 66%
“…There is accumulating evidence that microbes drive the development of protective Th1 or Th2 cells through their effects on APCs (1)(2)(3)(4). Dendritic cells (DCs) 3 are professional APCs that are present as immature sentinel cells that efficiently sample their environment for foreign Ag at potential sites of pathogen entry. Upon activation by signals released from the microorganisms or from infected tissues, sentinel DCs undergo maturation into potent T cell stimulatory effector DCs and migrate toward the T cell areas of draining lymphoid organs.…”
Section: Microbial Compounds Selectively Induce Th1 Cell-promoting Ormentioning
confidence: 99%
“…In a recent report of the effect of another helminth Ag, Acanthocheilonema viteae ES-62, on DC function in vitro, it was shown that ES-62 plus OVA-pulsed DC primed naive DO.11.10 CD4 T cells to become Th2-like (47). This occurred in the absence of significantly increased MHC class II expression or costimulatory molecule up-regulation.…”
Section: Discussionmentioning
confidence: 98%
“…If a Th2 response, e.g., to fungal hyphae (48) or to helminthic parasites (49), occurs in the environment of a lymph node, one might expect that the resulting T cell-derived IL-4 would skew all other ongoing or beginning immune responses toward a Th2 pattern. Our data would indicate that there may be some balancing mechanism ensuring that Th1 responses are not necessarily suppressed in an IL-4-rich milieu.…”
Section: Augmenting Effects Of Il-4: Relevancementioning
confidence: 99%